The role of brand awareness as an intervening variable in the effect of tiktok beauty content creator video reviews on consumer purchasing decisions - Choiriyah Adha; Miftah El Fikri (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to examine the effect of TikTok beauty content creator video reviews on consumer purchasing decisions, with brand awareness serving as an intervening variable. The research was motivated by the limited availability of foundation review content for medium-brown skin tones, which creates challenges for consumers in identifying suitable cosmetic products. A quantitative approach with a verificative design was employed, involving 100 followers of the TikTok account @austeniche selected through purposive sampling. Data were analyzed using multiple linear regression and Sobel mediation tests with SPSS 25. The findings reveal that video reviews have a positive and significant effect on brand awareness (t = 6.574, p lower than 0.001) and purchasing decisions (t = 3.138, p = 0.002). Brand awareness also significantly influences purchasing decisions (t = 6.067, p lower than 0.001). Furthermore, the Sobel test confirms that brand awareness significantly mediates the relationship between video reviews and purchasing decisions (t = 4.466, p lower than 0.001). These results demonstrate that informative and credible TikTok beauty content can effectively strengthen brand awareness and encourage consumer purchasing decisions, particularly for cosmetic products targeting consumers with medium-brown skin tones.